Divergent roles of PD-L1 in immune regulation during ischemia–reperfusion injury - Luo, Jianheng; Liu, Ke; Wang, Yong; Li, Hongge (Frontiers in Immunology, 2022)
Ischemia–reperfusion (I/R) injury is a type of pathological injury that commonly arises in various diseases. Various forms of immune response are involved in the process of I/R injury. As a member of the B7 costimulatory molecule family, programmed death 1-ligand 1 (PD-L1) is an important target for immune regulation. Therefore, PD-L1 may be implicated in the regulation of I/R injury. This review briefly describes the immune response during I/R injury and how PD-L1 is involved in its regulation by focusing on findings from various I/R models. Despite the limited number of studies in this field of research, PD-L1 has shown sufficient potential as a clinical therapeutic target.